Pengaruh Rasio Keuangan Terhadap Struktur Modal Pada Perusahaan Transportation and Logistics yang Terdaftar di BEI Surabaya - Maskurifah, Iis; Susanti, Hevi; Supriadi, Supriadi (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to analyze the effect of financial ratios partially and simultaneously affect the capital structure. The research method used is quantitative method with statistical analysis approach. In this study, the sampling used purposive sampling technique, namely based on predetermined criteria as many as 19 transportation and logistics companies on the Surabaya IDX in 2020-2023. The data analysis method was carried out using panel data regression analysis with Eviews 12. The regression model used is the Random Effect Model (REM) using the classical assumption test, T test, F test, and determination coefficient test. From the result of this test, it can be concluded that liquidity and profitability have no significant effect on capital structure. Firm size has a significant effect on capital structure. Simultaneous test result shows that liquidity, profitability, firm size have significant effect on capital structure.